CFD modelling of thermal distribution in industrial server centres for configuration optimisation and energy efficiency. (1st January 2014) - Paradis, Pierre-Luc; Ramdenee, Drishtysingh; Ilinca, Adrian; Ibrahim, Hussein
The use of servers for computational and communication control tasks is becoming more and more frequent in industries and institutions. Ever increasing computational power and data storage combined with reduction in chipsets size resulted in the increased heat density and need for proper configurations of the server racks to enhance cooling and energy efficiency. While different methods can be used to model and design new server centres and optimise their configuration, there is no clear guideline in the literature on the best way to design them and how to increase energy efficiency of existing server centres. This paper presents a simplified yet reliable computational fluid dynamics (CFD) model used to qualitatively evaluate different cooling solutions of a data centre and proposes guidelines to improve its energy efficiency. The influence of different parameters and configurations on the cooling load of the server room is then analysed.